Physical activity in the heat: thermoregulation and hydration: Supporting document to the Consensus Statement, Mexico City, February 1999 - Aragón Vargas, Luis Fernando (1999)
This document is not intended to be a thorough scientific review, but rather a useful source of information. While it is based on a sound, updated review of the scientific literature, the major intention is to provide clear statements and practical recommendations that are relevant to the Latin American population. The inquisitive reader is directed to recent excellent reviews on this topic. The document was prepared back in 1999 and has not been updated. It is included here as a record in English of the published paper in Spanish.